Development of E-LKPD Mathematics Using Liveworksheets with Malay Context - Syutaridho, Syutaridho; Nizar, Harisman; Ramadan, Dwi Cahya; Jufri, Khuzaimah Al; Fitri, Diana; Nuryasin, Ahmad Fikri (UNNES JOURNAL, 2025)
The combination of technology with local culture in this case the Malay context is a new thing in this study. One of the targets to be achieved is in the ability category, where learning independence, student mathematics, adaptive reasoning, student involvement, science literacy, assignments, mathematical connections, and teacher professionalism are presented in this study. A teacher must be the center of change in improving learning, how a teacher is able to utilize the context to design learning, where the use of context is not only as a learning ceremony but utilizes the context as a whole in an effort to build students' mathematical knowledge and also students' understanding of mathematical concepts. Education must also undergo a transformation in the Society 5.0 era. especially in mathematics learning, it is expected that learning can run in a blended learning manner. This study produces the objectives of E-LKPD mathematics using Liveworksheets with a Malay Context that is valid, practical and has a potential effect on mathematical problem solving abilities. This type of research is development research, which involves students at the junior high school level. The data for this study were obtained from the results of observations, interviews and tests. The results of this study are to produce a valid and practical Liveworksheets-based mathematics E-LKPD with a Malay context and the development of Liveworksheets-based mathematics E-LKPD with a Malay context in junior high schools that has been developed has a potential effect on students' problem-solving abilities based on the analysis that has been obtained, namely 67 students, 9 students have problem-solving abilities with a very high category, 19 students have problem-solving abilities with a high category, 18 have problem-solving abilities with a moderate category, 10 participants have problem-solving abilities with a category, 11 students have problem-solving abilities with a very low category. Then the average mathematical problem solving is 64.05, meaning that the developed E-LKPD has a moderate potential effect. This study contributes to the development of mathematics E-LKPD using liveworksheets that are more effective in overcoming students' difficulties in learning mathematics. Abstrak Perpaduan teknologi dengan budaya lokal dalam hal ini konteks melayu menjadi novelty dari penelitian ini. salah satu target yang akan digapai yaitu pada kategori kemampuan, dimana kemandirian belajar, matematis siswa, penalaran adaptif, keterlibatan siswa, literasi sains, penugasan, koneksi matematika serta keprofesionalan guru dimunculkan dalam penelitian ini. Seorang guru harus menjadi center perubahan dalam perbaikan pembelajaran, bagaimana seorang guru mampu memanfaatkan konteks untuk mendesain pembelajaran, dimana penggunaan konteks tidak hanya sebagai ceremony pembelajaran tetapi memanfaatkan konteks secara utuh dalam upaya membangun pengetahuan matematik siswa dan juga pemahaman konsep matematika siswa. Pendidikan juga harus mengalami transformasi di era Society 5.0. khususnya pada pembelajaran matematika diharapkan pembelajaran dapat berjalan secara blended learning. Penelitian ini bertujuan menghasilkan E-LKPD matematika menggunakan Liveworksheets dengan Konteks Melayu yang valid, praktis dan memiliki efek potensial terhadap kemampuan pemecahan masalah matematis. Jenis penelitian ini adalah penelitian pengembangan, yang melibatkan siswa di tingkat sekolah menengah pertama. Data penelitian ini diperoleh dari hasil observasi, wawancara dan tes. Hasil dari penelitian ini yaitu Menghasilkan E-LKPD matematika berbasis Liveworksheets dengan konteks Melayu yang valid dan prkatis serta Pengembangan E-LKPD matematika berbasis Liveworksheets dengan konteks Melayu di SMP yang dikembangkan memiliki efek potensial terhadap kemampuan pemecahan masalah peserta didik berdasarkan analisis yang telah diperoleh yaitu 67 peserta didik, 9 peserta didik memiliki kemampuan pemecahan masalah dengan kategori sangat tinggi, 19 peserta didik memiliki kemampuan pemecahan masalah dengan kategori tinggi, 18 peserta didik memiliki kemampuan pemecahan masalah dengan kategori sedang, 10 peserta didik memiliki kemampuan pemecahan masalah dengan kategori rendah, 11 peserta didik memiliki kemampuan pemecahan masalah dengan kategori sangat rendah. Kemudian rata-rata pemecahan masalah matematis sebesar 64,05 artinya E-LKPD yang dikembangkan memiliki efek potensial sedang. Penelitian ini memberikan kontribusi untuk pengembangan E-LKPD matematika menggunakan liveworksheets yang lebih efektif dalam mengatasi kesulitan siswa dalam belajar matematika.